Genomic comparison between two Inonotus hispidus strains isolated from growing in different tree species - Wang, Qingchun; Bao, Haiying; Li, Zhijun (Frontiers in Genetics, 2023)
Inonotus hispidus mainly growing in broad-leaved trees, including Morus alba, Fraxinus mandshurica, and Ulmus macrocarpa etc. The fruiting body of I. hispidus growing in M. alba (hereafter as MA) is used as a traditional Chinese medicine "Sanghuang", which has anti-tumor, antioxidation, anti-virus and other effects. However, differences between the genetic material basis of I. hispidus growing in other tree species have not been reported. Therefore, in this paper, the genomic comparison between MA and I. hispidus growing in F. mandshurica (hereafter as FM) were studied. The whole genome of MA monokaryon was sequenced by Illumina combined with Pac Bio platform. Next, genome assembly, genome component prediction and genome functional annotation were performed. Comparative genomics analysis was performed between FM monokaryon and MA monokaryon, using MA as the reference. The results showed that, MA had 24 contigs with a N50 length of 2.6 Mb and a genome-wide map of 34.14 Mb was drawn. Specifically, MA contained 8,356 coding genes, 8,387 repeat sequences and 97 ncRNAs. Furthermore, 5,342, 6,564, 1,595, 383, 123 and 15 genes were annotated from GO, KEGG, KOG, CAZymes, CYP450 and gene clusters of secondary metabolites, respectively. In addition, 9 major secondary metabolic pathways, 31 signal transduction pathways, 14 xenobiotics biodegradation and metabolism pathways, 148 CAZymes families and 12 key enzymes involved in the "Terpenoid backbone biosynthesis" MVA pathway were identified in MA genome. Moreover, comparative genomics showed that, the coding genes, repeat sequences and total number of genes annotated in different databases of FM were higher than that of MA. At the same time, there were 228,256 SNPs, 275 InDels and 9,020 SVs between MA and FM, and 6,499 collinear regions. This study provides a research foundation for the medicinal application of FM as MA from the perspective of genetic composition.